Development of Cellulose Eco-Nanocomposites with Antimicrobial Properties Oriented for Food Packaging - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (2013)
Nanocomposites based on cellulose acetate, a commercial organoclay (Cloisite30B), triethyl citrate and variable content of antimicrobial agents (thymol and cinnamaldehyde), were obtained using a solution casting technique. The properties of the nanocomposites were evaluated using X-ray diffraction, differential scanning calorimetry, thermogravimetric analysis, mechanical (modulus of elasticity, tensile strength and elongation at break), scanning electronic microscopy, global migration and microbiological testing. A reduction of glass transition (Tg), melting temperature (Tm) and melting enthalpy (†Hm) was also observed when the content of thymol and cinnamaldehyde was increased in the cellulose acetate nanocomposites. In contrast, thermal stability, mechanical performance and morphology of material did not show important differences when the content was modified. Results of global migration were dependent of the kind of simulant used. Finally, the antimicrobial activity was dependent of the essential oil used and its content inside the nanocomposite. An important effect of organoclay on the antimicrobial activity was also observed. Copyright © 2012 John Wiley & Sons, Ltd.